Elevated De Ritis Ratio Is Associated With Poor Prognosis in COVID-19: A Systematic Review and Meta-Analysis - Pranata, Raymond; Huang, Ian; Lim, Michael Anthonius; Yonas, Emir; Vania, Rachel; Lukito, Antonia Anna; Nasution, Sally Aman; Siswanto, Bambang Budi; Kuswardhani, Raden A. Tuty (Frontiers in Medicine, 2021)
Objective: This meta-analysis aims to assess whether elevated De Ritis ratio is associated with poor prognosis in patients with coronavirus 2019 (COVID-19). Methods: A systematic literature search was performed using PubMed, Embase, and EuropePMC databases up until September 17, 2021. De Ritis ratio is also known as Aspartate aminotransferase/alanine transaminase (AST/ALT) ratio. The main outcome was poor prognosis, a composite of mortality, severity, the need for ICU care, and intubation. The effect measure was odds ratios (ORs) and mean differences. We generated sensitivity and specificity, negative and positive likelihood ratio (NLR and PLR), diagnostic odds ratio (DOR), and area under curve (AUC). Results: There were eight studies with 4,606 patients. De Ritis ratio was elevated in 44% of the patients. Patients with poor prognosis have higher De Ritis ratio [mean difference 0.41 (0.31, 0.50), p < 0.001; I2: 81.0%] and subgroup analysis showed that non-survivors also have higher De Ritis Ratio [mean difference 0.47 (0.46, 0.48), p < 0.001; I2: 0%]. Elevated De Ritis ratio was associated with poor prognosis [OR 3.28 (2.39, 4.52), p < 0.001; I2: 35.8%]. It has a sensitivity of 55% (36–73), specificity of 71% (52–85), PLR 1.9, NLR.63, DOR of 3 (2–4), and AUC of.67 (0.63–0.71). The posterior probability of poor prognosis was 38% if De Ritis is elevated, while 17% if De Ritis is not elevated. Conclusion: Elevated De Ritis ratio is associated with poor prognosis in patients with COVID-19. Systematic Review Registration: PROSPERO ID: CRD42020216634.